Women's expectations and experiences of labor induction - a questionnaire-based analysis of a randomized controlled trial - Moa Strandberg; Tove Wallstrom; Eva Wiberg-Itzel (BMC, 2021)
Abstract Background Although labor induction is a commonly used procedure in obstetrical care, there are limited data on its psycho-emotional effects on the woman. This study analysed the expectations and experiences of women in different routes of labor induction. The study's primary aim was to compare women's delivery experience if induced by orally administrated misoprostol (OMS) compared with misoprostol vaginal insert (MVI). Secondly, an evaluation of women's general satisfaction with induced labor was made, and factors associated with a negative experience. Methods Primiparous women (n = 196) with a singleton fetus in cephalic presentation, ≥ 37 weeks of gestation, with a Bishop's score ≤ 4 planning labor induction were randomly allocated to receive either OMS (Cytotec®) or MVI (Misodel®). Data were collected by validated questionnaires, the Wijma Delivery Expectation/Experience Questionnaire (A + B). The pre-labor part of the survey (W-DEQ version A) was given to participants to complete within 1 hour before the start of induction, and the post-labor part of the questionnaire (W-DEQ version B) was administered after birth and collected before the women were discharged from hospital. Results It was found that 11.8% (17/143) reported a severe fear of childbirth (W-DEQ A score ≥ 85). Before the induction, women with extreme fear had 3.7 times increased risk of experiencing labor induction negatively (OR 3.7 [95% CI, 1.04-13.41]). Conclusion No difference was identified between OMS and MVI when delivery experience among women induced to labor was analysed. Severe fear of childbirth before labor was a risk factor for a negative experience of labor induction. Trial registration Clinical trial register number NCT02918110 . Date of registration on May 31, 2016.